2022
DOI: 10.1093/gerona/glac070
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Ultra-Processed Food and Cognitive Decline among Older Adults With Type-2 Diabetes

Abstract: Background Ultra-processed food (UPF) consumption is related to increased morbidity and mortality. However, knowledge on its association with cognitive function is lacking. In this longitudinal study, we examined the associations between UPF intake and cognitive decline in older adults with type-2 diabetes (T2D). Methods The sample included initially non-demented T2D older adults (≥65y), from the Israel Diabetes and Cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…The consumption of ultra-processed foods, which are usually high in calories, sugar, trans fats and salt, has been connected to faster cognitive decline in later life (Weinstein et al, 2022), as well as to mood disorders (Lane et al, 2022). In contrast, a high quality diet may help to protect people from cognitive decline (Smyth et al, 2015).…”
mentioning
confidence: 99%
“…The consumption of ultra-processed foods, which are usually high in calories, sugar, trans fats and salt, has been connected to faster cognitive decline in later life (Weinstein et al, 2022), as well as to mood disorders (Lane et al, 2022). In contrast, a high quality diet may help to protect people from cognitive decline (Smyth et al, 2015).…”
mentioning
confidence: 99%
“…A prior study that investigated the association of UPF and cognition in 568 individuals with type 2 diabetes found no association between total calorie consumption of UPF and cognitive decline, likely because of the small sample size or reverse causation, since individuals who develop diabetes could have reduced their UPF consumption after diagnosis. Our findings are in line with 2 recent studies that investigated the association between UPF consumption and cognition.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are in line with previous studies linking consumption of UPF and adverse health outcomes, such as the increased risk of overweight and obesity, 38,39 metabolic syndrome, 40 cancer, 41 cardiovascular diseases, 42 and allcause mortality. 43,44 A prior study 21 that investigated the association of UPF and cognition in 568 individuals with type 2 diabetes found no association between total calorie consumption of UPF and cognitive decline, likely because of the small sample size or reverse causation, since individuals who develop diabetes could have reduced their UPF consumption after diagnosis. Our findings are in line with 2 recent studies 22,23 that investigated the association between UPF consumption and cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, no correlation was identified between the consumption of sugary drinks and incidence of AD. Other studies investigating the consumption of artificially sweetened beverages also demonstrated associations with health outcomes, such as a higher risk of cancer ( 35 ) and mortality from cardiovascular disease ( 36 ), however, results are controversial. More studies assessing the effect of consuming artificially sweetened beverages on health outcomes, including cognitive decline and AD, should be conducted.…”
Section: Discussionmentioning
confidence: 99%